Strategic consultant's competency circle - Hamed Dehghanan; Hossein Rahmanseresht; Vahid KhasheiVarnamkhasti; Mohammad Vakili (کاوش‌های مدیریت بازرگانی, 2022)
Introduction: The management consulting industry, with a total global value of approximately $ 285 billion, is one of the largest and most flourishing markets in the professional services industry. An analysis of the last five decades indicates that the development of the management consulting industry has been closely related to the developments in the global economy during the past years. Management consulting as one of the sub-branches of knowledge-based business services has had a higher growth than the other sub-branches in this field.So far, just a few studies have been conducted on the success factors of strategic management consultants and their consequences. The issue of management competency has widely been considered by researchers, but the competency of management consultants have been less addressed. The purpose of this study is to investigate the competencies of strategic management consultants.Methodology: The research method is qualitative and in accordance with the emerging Glaser’s grounded theory. The experts in this research consisted of 21 professionals in the field of management consulting, especially strategy consultants, who were selected through purposeful sampling, and semi-structured interviews were used for data collection. The MAXQDA software version 10 and the triple coding approach were used for data analysis.Results and Discussion: As many as 992 codes were found in the first stage (open coding). After the elimination of the repeated or poor codes, 525 pure codes were left. The results indicated that strategic management consultants should have a set of general and specific competencies. General competencies are divided into three groups including individual and characteristic competencies, managerial competencies, and consulting competencies. Specific competencies are a set of competencies related to strategic management and management consulting. A total of 25 key competencies were identified, and their relative importance was analyzed based on the number of repetitions of the categories and their frequency. These competencies were eventually demonstrated in a model called the Strategy Consultant Competency Circle, which can serve as a good basis to assess strategy consultants and assist clients in selecting the best consultants.Among five major competency categories, strategic management competencies are the most frequent. This category includes competencies as the deep knowledge of strategic management, strategic thinking, change of management skills and environmental mastery, which means being aware of the best practices of the industry, knowing about competitive environment and consumer behavior, and so on.Specific consulting management competencies are in the second rank according to frequency. This category includes competencies such as leading the leaders, project management, problem solving, flexibility and organizational coexistence (i.e, to be approved as a member of the organizational family). Of course, theses competencies are common among all the management consultants in any field such as strategy, HR, marketing, and so on.The third category includes characteristic competencies such as being achievement-oriented (i.e. management consultant should be a model of success), learning appetite, self-control, being loved, self-confidence, intelligence and personal maturity.The fourth category includes general management competencies such as basic management skills, ability to integrate, general information, knowledge of management and organization, and at last economic intuition.Finally, there is the category of general consulting competencies. They are vital not only for management consultants but also for consultants in other fields such as psychology, legal, and so on. This category includes effective communication, verbal skills, professional ethics and mindfulness. So, we have 25 competencies in five categories.Conclusion: The proposed circle model has several various remarkable benefits. First, it helps to understand the basis and origin of competencies. Second, it shows, to some extent, the ability to compare the competencies of strategy consultants with other groups of individuals with whom they have some commonalities, such as strategic managers, management consultants in other areas, consultants and managers. Third, this model provides a good blueprint to determine the competencies of groups related to strategy consulting. For instance, in the case of a human resources consultant and based on this model, four parts of the circle can be used exactly (although the objective examples of some of these competencies may be different). It is also enough to remove the strategic management competencies and identify and replace specific human resource management competencies.The present study clearly shows that the effectiveness of strategy consulting depends on the acquisition of a wide variety of competencies. It is now possible to better understand why a high percentage of strategy consulting projects fail. Acquiring the 25 competencies proposed for strategy consultants requires the implementation of various training and development programs, the gap of which is currently well felt in our country. Therefore, the major suggestion of this research is to launch professional training courses for strategy consultants to provide the human capital needed in this field.